WHO SPEAKS LOUDEST? EXPLORING THE DYNAMICS OF STUDENTS' VOICES IN THE DIGITAL AGE WITH WIZER.ME IN MODERN TEACHING - Khoirunnisaa', Try Ammalia; Maghfiroh, Naily Inayatul; Mustofa, Mutmainnah (English Review: Journal of English Education, 2023)
This study emphasizes the need for digital adaptation in contemporary teaching techniques and recommends utilizing the website Wizer.me as an effective instrument to achieve this need. Exploring the dynamics of students' voices in the digital age with Wizer.me in modern teaching is the topic of this study. The study is to investigate students' perspectives on the Wizer.me platform in teaching and learning, as well as its integration with conventional teaching techniques. This study used survey research method. The participants were seventh-grade students at SMPI Almaarif 01 Singosari Malang. According to the study, Wizer.me is an online learning platform that has a positive impact on student engagement, and personalized learning and promotes student-centered learning. The data will be statistically analyzed using descriptive techniques. The result indicated that 86,7% of students had utilized Wizer.me for their assignments, 100% of students liked using this platform, and 33,3% of students frequently use Wizer.me more than two times. Moreover, 73.3% of students preferred using the Wizer.me platform over traditional methods in the learning process, and 100% of students agree that they understand better acquiring the material using this platform than traditional techniques. Hopefully, the study's findings will be of major benefit to educators and those involved in the integration of educational technology, supporting breakthroughs and improvements in the learning environment